Automatic Medicine Dispenser Using QR Code - Chinmay Prashant Tawde; Beena Ballal; Makarand Nagvekar; Mohammed Ahtesham Shaikh; Vaishnavi Phatkare (International Journal of Solid State Innovations & Research, 2025)
The "Automatic Medicine Dispenser Using QR Code" revolutionizes healthcare by minimizing queue-related inconveniences through automated medicine dispensing. It integrates software for QR-based prescription management and hardware components like Arduino Mega 2560, IR sensors, and motors for precise dispensing. Additionally, it ensures real-time doctor notifications for medicine unavailability, enabling timely alternatives and uninterrupted patient care. The study comprises two teams, each dedicated to software and hardware development. On the software front, one system manages the Medicine Vending Machine (MVM) while the other generates doctor prescribed QR codes. Hardware components include Arduino Mega 2560, motors, IR sensors, Bluetooth modules, and more, facilitating precise medicine dispensing. Beyond conventional automation, the study tackles medicine unavailability. When a prescribed medicine is unavailable, the system immediately notifies the doctor, enabling swift action to prevent treatment delays. This real-time communication allows doctors to prescribe alternative medications or issue new prescriptions, ensuring patients receive timely and uninterrupted care. Key challenges include managing a diverse range of medicines, suggesting suitable generic substitutes, maintaining an optimized inventory, and seamlessly onboarding doctors into the system. By integrating automation, real-time updates, and efficient inventory management, the study represents a transformative shift in healthcare, enhancing accessibility, accuracy, and patient-centric service while significantly improving the overall efficiency of the medical dispensing process.
Keywords: Arduino Mega; IOT; QR code; Smart Health Technology; Vending machines; Wireless